Dilemmas of engagement evaluation and the new public management - Kushner, Saville; Norris, Nigel (Advances in program evaluation, 2007)
In our reforming public institutions it sometimes feels as though the very ground of social and political contracts is shifting. The economic revolution embraced by neo-liberals and neo-conservatives is paralleled by a governance revolution in those same institutions which were designed to protect us from historical swings and ideological roundabouts. Our public institutions - for the most part the public sector and its professional groups - in the eyes of some provided stability, while for others they were a brake on change. Now, however, they have become conduits for political change and reform. We live in an institutional world now dubbed the New Public Management (NPM). In this new landscape evaluators might have to think afresh about how to position ourselves in relation to institutional ethics and the pursuit of social justice. In this volume contributors give us a start in thinking through such a repositioning, some within the values framework of NPM, others as external observers.